BLENDED PEDAGOGIES IN PRACTICE: INTEGRATING GOOGLE CLASSROOM FOR ANDRAGOGICAL ENGLISH LANGUAGE INSTRUCTION IN EFL CLASSROOMS - B, Simila; R. Abilasha (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The integration of blended learning has revolutionised traditional teacher-centred pedagogy by introducing an andragogical, learner-centred approach that promotes independence and digital fluency in English as a Foreign Language (EFL) classrooms. This shift has moved educational environments beyond face-to-face interactions, leveraging platforms like Google Classroom to facilitate continuous access to assignments, quizzes, multimedia lectures, and interactive feedback. Such digital tools not only support flexible and reusable learning but also align with evolving student expectations for standardised and accessible educational inputs. In parallel, initiatives like the Tamil Nadu government’s Nan Mudhalvan programme exemplify efforts to place learners at the core of educational innovation, fostering digital competence and modular citizenship. This paper explores the impact of blended learning and andragogical methods in enhancing EFL teaching and learning processes within technologically enriched environments.